Analysis of seismic changes rate based on the seismotectonic spatial distribution of West Sumatra region - Wela Yulianda; Syafriani Syafriani; Ardiyansyah Sabarani (PILLAR OF PHYSICS, 2017)
West Sumatra has a high level of seismicity so as often rocked by significant earthquakes and caused damage. The earthquake is usually preceded by symptoms such as occurrence of a seismic Quiescence phenomenon. This phenomenon can be seen by observing seismic rate changes in a region. The observation used data from NEIC / USGS and ISC with time period from 22nd of September 1918 to 31st of October 2015. The method used to analyze the seismic rate changes is the z-value method. The study area is divided into several grids. Z-value of each grid is counted and will be spatially distributed so seismic rate change of West Sumatra can be analyzed. This analysis will show presence or absence of seismic Quiescence phenomenon before earthquake in West Sumatera. The observation result showed that there is a certain preceding phenomenon before the significant earthquake in 1943 (7.8 SR) and 2007 (7.8 SR) in West Sumatra. This phenomenon called seismic Quiescence can be used as earthquake precursor. At the beginning of 2015 showed the decrease in seismic activity in several regions in West Sumatra according to development of seismic activity data. It is suspected as early symptoms of impending significant earthquake in future